Medical Spanish Endocrinology Educational Module - Pilar Ortega; Christian González; Itzel López-Hinojosa; Yoon Soo Park; Jorge A. Girotti (Association of American Medical Colleges, 2022)
Introduction Hispanic/Latinx patients experience health disparities in endocrine disease, such as higher rates of mortality due to diabetes mellitus, worse outcomes in the surgical treatment of thyroid cancer, and lack of knowledge about bone health and osteoporotic fracture prevention. Educational strategies to teach cultural and linguistic medical Spanish knowledge to medical students have the potential to improve Hispanic/Latinx endocrine health. Methods We created an 8-hour medical Spanish endocrine module targeting language and cultural skills acquisition. Specifically, students practiced obtaining a past medical history, obtaining a medications history, providing and explaining a diagnosis, explaining discharge instructions, and discussing sociocultural aspects of endocrine health. We divided the module into four 2-hour sessions: (1) preclass self-study, (2) class period, (3) role-play/interviewing practice session, and (4) case/cultural activity assignment. Participants completed a pre- and postassessment to measure student confidence level and knowledge. Results We implemented the module four times at one medical school, with 47 fourth-year medical students with intermediate or higher general Spanish skills. Confidence increased for all learners in the endocrine-focused interview and exam in Spanish. Heritage Spanish learners, who were exposed to Spanish at home as children, reported higher postmodule confidence in eliciting the past medical history of endocrine problems. Discussion The medical Spanish endocrine module improved the communication skills of medical students with intermediate through advanced Spanish proficiency. Future study should evaluate learner clinical performance metrics and applications to other groups of learners, such as resident physicians or health professions involved in the care of patients with endocrine disease.